Field notes from a fungi forager : an illustrated journey through the world of Pacific Northwest mushrooms - Rodriguez, Ashley (Sasquatch Books, 2024)
"Gifty, regional, illustrated mushroom guide, including profiles, fun facts, regional info and general info"--